TI_GERICHTE 16.2019.63 vom 18. Juni 2020 , Risarcimento del danno a norma dell'art. 679 CC: prova dell'entità del danno - TI Tribunale d'appello (2020)
Risarcimento del danno a norma dell'art. 679 CC: prova dell'entità del danno